Art Festival: Student Program Field Studies and Community Service in Enhancing Community Spirit in Nagori Bukit Rejo Village, Simalungun Regency - Muniruddin; Maysaroh; Mawar Ayuni; Anisa Hafizah Siregar; Hikmatul Fadhilah Nst; Iga Nailah Aulia BR Lubis; Eka Septiana; Putri Khofifah Rambe (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The purpose of this study is to examine how the art festival organized by students participating in the Community Service Program (KKN) of the State Islamic University of North Sumatra in Nagori Bukit Rejo serves to enhance social interaction, promote diversity, and encourage the development of the village community. This research was conducted using qualitative methods with a Participatory Action Research (PAR) approach, which involved observation, interviews, and documentation during the Art Festival activities. The results of the study show that the art festival not only serves as a place of entertainment, but also as a social and educational tool that can help strengthen solidarity among residents across age, ethnicity, and religion. Overall, the art festival helps preserve local culture, foster a sense of community, and raise awareness of the importance of diversity in social life.